Talk Show Program as an Effort to Build Brand Awareness of Udayana University Hospital's Instagram - Wirya Pratama, I Wayan Agus; Gede Utara Hartawan, I Gusti Agung; Rusca Putra, Kuswantoro (Jurnal Kedokteran Brawijaya, 2022)
Non-Covid-19 service closure has formed a stigma that hospitals only serve Covid-19 patients. This condition affects brand awareness and decreases the number of hospital visits. An interactive talk show using Instagram can be used to reintroduce hospital services to the public. This study aimed to measure the success of the talk show program in building brand awareness of Udayana University Hospital's Instagram account. One group pretest-posttest research was carried out at Udayana University Hospital on October 7, 14, and 21, 2021, by intervening with the Instagram content of Udayana University Hospital. After the live broadcast ended, the talk show content was published on the Instagram feed. The success of the talk show program was seen by comparing the audience growth, engagement rate, and brand awareness measurements before and after the talk show took place. Brand awareness can be seen in profiles, post-impressions, and profile visits to the Instagram account. The highest post-engagement (36.46%) was obtained in the first episode of the talk show and was in the very high category. Instagram followers and engagement rates increased and categorized very high. Profile impressions and visit profiles increased, indicating a wide range of content on the Udayana University Hospital's Instagram account. This study shows that talk show program can be implemented as a routine program that builds brand awareness on the Instagram account of Udayana University Hospital. This program can be used as a solution to introduce Udayana University Hospital to Instagram users by inviting quality guest stars and using easy-to-understand material.